Mercury Isotopes in Shale Gas From Wufeng-Longmaxi Shale Formation of Sichuan Basin, Southern China: A Preliminary Investigation - Tang, Shunlin; Ding, Yuxiang; Zhu, Guangyou; Feng, Xinbin; Zhang, Huaishun; Li, Penggao (Frontiers in Earth Science, 2022)
A series of investigations have been achieved in the study of traditional stable isotopes and rare gas stable isotopes in natural gas. However, little is known about non-traditional stable isotopes of mercury in natural gas, especially in shale gas developed and utilized in recent years. In fact, the presence of mercury in natural gas (including shale gas) provides a basis for mercury isotopes research. Mercury was extracted from the shale gas of Wufeng-Longmaxi formations in the YS108 block of Zhaotong National shale gas demonstration area in Sichuan Basin by using an acid potassium permanganate solution, and then followed by analyzing mercury content and stable isotope composition of mercury. The mercury content in marine shale gas of Wufeng-Longmaxi formations ranges from 171 to 2906 ng/m3, with an average of 1551.079 ± 787.08 ng/m3 (n = 37, 1SD). The Δ199Hg values of mercury stable isotopes range from 0.02 ‰ to 0.39‰, with an average of 0.22 ‰ ± 0.08 ‰ (n = 37,1SD), and the δ202Hg values range from -1.68‰ to -0.04 ‰, with an average of -0.87 ‰ ± 0.31 ‰ (n = 37,1SD), which are significantly different from the Δ199Hg and δ202Hg information of coalbed gas, but similar to the Δ199Hg and δ202Hg information of terrestrial oil-type gas and the Δ199Hg in the main hydrocarbon-forming organic matter of lower organisms such as algae (t Test, p > 0.05). It indicates that the terrestrial target strata with abundant algae or the strata with positive Δ199Hg are the target strata for the exploration of terrestrial oil and gas.